A comparative study on mechanical properties of carbon and Kenaf composites via vacuum infusion technique - Yusuff, Mohamad Ikhwan; Sarifuddin, Norshahida; Mohd Ali, Afifah; Mohd Daud, Farah Diana; Mohamad Badari, Siti Norbahiyah (Penerbit Universiti Sains Malaysia, 2020)
The growth of polymer-based composites from either synthetic or natural fibres, especially carbon and kenaf fibres as reinforcement, has gained major interest in many pieces of research. However, only a little attention has been made that compared the mechanical performances of these developed composites based on previous studies. In fact, this comparative study is essential to identify the mechanical gaps between synthetic and natural fibres. Thus, the current work is aiming to provide a comparative study on mechanical properties of manufactured composite materials from both synthetic and natural fibres in which carbon and kenaf fibres were used as reinforcing agents, whereas epoxy resin acts as a matrix phase that fabricated via vacuum infusion method. The thickness and fibre loadings of fabricated composite materials were fixed at 3 mm and 40 vol. %, respectively. The investigations focused on the mechanical performances of carbon and kenaf composites under tensile and flexural tests. The result shows that tensile and flexural strengths for carbon composite were attained at 399.05 MPa and 362.29 MPa, respectively. Meanwhile, for kenaf composite, the tensile strength was gained at 77.28 MPa, whereas, the flexural strength was obtained at 61.24 MPa.